Investigating the Effects of Democratic Leadership Style and Compensation on Indonesian Civil Servants' Performance - Siahaan, Rumiris; Sinurat, Mangasi; Rusmewahni, Rusmewahni; Jayanti, Suci Etri; Ilham, Rico Nur (Indonesia Academia Research Society, 2024)
Employee performance is the outcome of a process measured over a specific period on the basis of predetermined provisions or agreements. Generally, performance can be interpreted as an individual's entire work process, with results as a basis for determining whether their work is satisfactory. This study investigated the influence of democratic leadership style and compensation on employee performance at the Office Secretariat of the Regional People's Representative Council of the Serdang Bedagai Regency. The study employed a quantitative data method to determine the research focus, select informants as sources, assess data quality, analyse and interpret data, and draw conclusions from the findings. The findings reveal that work status and work environment influence employee performance. Besides that, democratic leadership style and compensation did not demonstrate a significant impact. However, when considered collectively, all four factors were found to influence employee performance. These results provide valuable insights for organisational management to understand and improve employee performance within this context.